Antimicrobial, computational, and molecular docking studies of Zn (II) and Pd (II) complexes derived from piperidine dithiocarbamate. (25th November 2020) - Al‐Janabi, Ahmed S.M.; Kadhim, Mustafa M.; Al‐Nassiry, Amenah I.A.; Yousef, Tarek A.
Abstract : Mixed ligand complexes of Zn (II) and Pd (II) have been prepared from piperidine dithiocarbamate (PipDT) and amine ligand {2, 2′‐bipyridine (Bipy), 1, 10‐phenanthroline (Phen), and 3‐aminopyridine (3Apy)} to afford complexes of the type [M( κ 1 ‐PipDT)( κ 2 ‐Bipy)] {M II Zn, Pd} (1, 4 ), [M( κ 1 ‐PipDT)( κ 2 ‐Phen)] (2, 5 ), and [M( κ 1 ‐PipDT)( κ 1 ‐3Apy)2 ] (3, 6 ). The reaction of equivalent molar of sodium benzisothiazolinate (Nabit) or sodium saccharinate (Nasac) with cis ‐[PdCl2 (PPh3 )2 ], followed by addition, sodium piperidine dithiocarbamate (NaPipDT) afforded complexes of the type trans ‐[Pd( κ 1 ‐PipDT)( κ 1 ‐N‐bit)(PPh3 )2 ] (7 ) and trans ‐[Pd( κ 1 ‐PipDT)( κ 1 ‐N‐sac)(PPh3 )2 ] (8 ). The obtained complexes were characterized by elemental analysis and spectroscopic techniques. The PipDT − was bonded as monodentate fashion via sulfur atom, whereas the diamine ligands were coordinated as bidentate chelating, while the 3Apy ligand bonded as monodentate mode through the nitrogen of heterocyclic ring. In complexes (7 ) and (8 ), the bit − and sac − ligand coordinated as monodentate through the nitrogen atom of heterocyclic ring. The antimicrobial activity of the complexes was tested. All the complexes showed moderate to good activity compared with standard antimicrobial. Moreover, the calculations of the density functional theory (DFT) were performed to estimate the thermal parameters, dipole moment, polarizability, and molecular electrostatic potential of the present complexes; in addition, Mulliken atomic charges of the complexes, total electron density (TED), electrostatic surface potential (ESP), lethal concentration (LC50 ), and docking studies as well as the descriptors of chemical reactivity were studied. Abstract : Mixed ligand complexes of Zn (II) and Pd (II) derived from piperidine dithiocarbamate and amine or heterocyclic ligands have been characterized by elemental analysis and spectroscopic techniques. The antimicrobial activity of the complexes was tested. Moreover, the calculations of the DFT were performed to estimate the thermal parameters, dipole moment, polarizability, and molecular electrostatic potential; in addition, Mulliken atomic charges, total electron density, electrostatic surface potential, lethal concentration, and docking studies as well as the descriptors of chemical reactivity were studied.